Synthesis and Supramolecular Structure of 1-(4-{[(E)-3,5-Dibromo-2-hydroxybenzylidene]amino}phenyl)ethanone O-benzyloxime - Zhao, Li; Guo, Hong-Xia; Sun, Yin-Xia; Meng, Wei-Sheng; Yang, Cheng-Juan; Zhang, Xin-Yiang (Asian Journal of Chemistry, 2013)
The compound, 1-(4-{[(E)-3,5-dibromo-2-hydroxybenzylidene]amino}phenyl)ethanone O-benzyloxime, has been synthesized by ({4-amino}phenyl)ethanone O-benzyloxime and 3,5-dibromosalicylaldehyde in ethanol solution and characterized by X-ray crystallography. There is one fairly strong intramolecular O1-H1···N2 hydrogen bond. In the crystal structure, each compound is linked to two other molecules into an infinite 1D supramolecular chain via Br···O interactions [3.354(4) Å].